Biophysics of DNA-Protein Interactions From Single Molecules to Biological Systems - Williams, Mark C.; Maher, III, L. James (Biological and Medical Physics, Biomedical Engineering, 2011)
This book presents a concise overview of current research on the biophysics of DNA-protein interactions. A wide range of new and classical methods are presented by authors investigating physical mechanisms by which proteins interact with DNA. For example, several chapters address the mechanisms by which proteins search for and recognize specific binding sites on DNA, a process critical for cellular function. Single molecule methods such as force spectroscopy as well as fluorescence imaging and tracking are described in these chapters as well as other parts of the book that address the dynamics of protein-DNA interactions. Other important topics include the mechanisms by which proteins engage DNA sequences and/or alter DNA structure. These simple but important model interactions are then placed in the broader biological context with discussion of larger protein-DNA complexes . Topics include replication forks, recombination complexes, DNA repair interactions, and ultimately, methods to understand the chromatin context of the cell nucleus. This book will be of interest to readers who wish to explore current biophysical approaches to DNA-protein interactions across multiple levels of biological complexity.